Vous êtes sur la page 1sur 8

1.

Given

+ =0 (a)

+ =0 (b)

wherein the roots in (a) are and and roots in (b) are and 2 .

This implies that

= +

= + 2
2

Furthermore, by rearranging the equations for p and q, we have

= = 2( 2 )

= =
2 4

Thus,

= 2( 2 )

=
2 4

Working on these two equations, we can express and in terms of p and q.

2
=
3
4 2
=
3

Going back to r, we can express it as

4 2 2
= =
3 3
2 2
= 2
3 3
2
= (2 )(2 )
9
Therefore, the value of r is ( )( ).

2. B

Since the ratio given for the sides of the triangle are 1: 3: 2, then the triangle can be classified as a 30-
60-90 triangle.

Recall that for any triangle that can be expressed as 1 , 3 and 2 , the angles opposite them are 30,
60, and 90, respectively. Thus, taking the ratio of the three angles, we have 30:60:90 = 1:2:3.

3. D

Given that sin (cot (1 + )) = cos(tan( )), we must find x.

We must recall the following Trigonometric Identities:

1
sin(cot )=
1
+1

1
cos(tan )=
1 +

Using these identities, we can express the original equation as

1 1
=
1 1 +
+ 1 (1 + )
(1 + )

Placing (1 + ) inside the radicand, we have

1 1
=
(1 + ) + 1 1 +

Squaring both sides and further simplifying the equation,

1 1
=
(1 + ) + 1 1+

1+ = (1 + ) + 1

1+ =1+2 + +1

We can cancel in both sides and rearrange the equation.


2 = 1

1
=
2

Hence, we have x = -1/2.

4. A

Given,

2 2 =2

2 + =4

+ + =4

For the systems of equation to have no solutions, then the determinant must equal to zero. Thus, from
the given equations, we have

2 1 2
det 1 2 1 = 0
1 1

Working on the matrix, we have

2( 1 4) 1(2 2 ) + 2(4 + 1) = 0

Simplifying this, we have

2 = 6

= 3

Thus, the value of is -3.

5. C

Given the equation of the line: 2 + 6 = 2 and hyperbola: 2 = 4, we need to look for its
point of contact. Thus, we are looking for a common point for both equations.

From the equation of the line, we can express x as

2 + 6 = 2

2 = 2 6
6
=1
2

Substituting this into the equation for our hyperbola, we get

6
(1 ) 2 =4
2
6
1 6 + 2 =4
4

4 46 + 6 8 = 16

2 + 46 + 12 = 0

+ 26 + 6=0

Since we have a quadratic equation in y, we can utilize the quadratic formula

4
=
2

with a =1, b = 26 and c = 6. Thus, we have

26 (26) 4(1)(6)
=
2(1)

Simplifying this, we arrive with

26
= = 6
2

Going back x, we have

6
= 1
2

6
=1 6 = 4
2

Therefore, the point of contact of both equations is (4, ).

6.

Given the equation 2 + 4 + 6 21 = 0 and the sum of the two roots is zero, we need to
find the roots.
Observe that if two numbers add up to zero, that means they are each others additive inverse.

If we let the first root be , then the second root must be .

Remainder Theorem states that the remainder when f(x) is divided by (x-r) is just equal to f(r).

So, since and are roots, then f( ) and f( )must both be equal to zero.

Thus, we have

2 + 4 +6 21 = 0

+2 + 4 6 21 = 0

Adding both equations, we arrive with

2 +8 42 = 0

+4 21 = 0

( + 7)( 3) = 0

Hence,

=3

(since = 7 leads to extraneous roots)

Furthermore, if and are roots then we it can be said that ( ) and ( + ) are factors of
( )= 2 + 4 + 6 21. That implies that ( )( + ) = = ( 3)

is a factor of ( ).

That means

( )= 2 + 4 + 6 21 = ( 3) ( )

where ( ) is the remaining trinomial factor of ( ) and can be expressed as ( ) = + + .

Observe that for ( ) to have -21 as its last term, the only way for that to happen is when C = 7. Also,
A= 1 since we have to consider ( 3).

Writing this down, we have

( )= + +7

Thus,

( )= 2 + 4 + 6 21
= ( 3)( + + 7)

= + + 4 3 21

Hence, = 2 and ( ) = 2 + 7. So going back we have

( )= ( 3)( 2 + 7) = 0

To get the roots, we have

( 3) = 0

= 3

And for

( 2 + 7) = 0,

We can utilize the quadratic formula and arrive with

(2) (2) 4(1)(7)


=
2(1)

4 4 28 4 26
= =
2 (-3, 2) 2

= 2 6

Therefore, the roots of ( ) are { , }.

7. Given E1 to be the ellipse passing through

+ =1
9 4

and is inscribed in a rectangle, we can see that ends of the major and minor axes are located at (3, 0)
and (0, 2). If E1 is inscribed in a rectangle, then the four vertices of the rectangle must be in (3, 2).

For illustration, (-3, 2) (3, 2)

(-4, 0) (4, 0)

(3, -2)
(-3, -2)
Thus, the second ellipse passing through (0,4) must satisfy the general equation for second degree
equation which is, in general, expressed as

+ 2 + + 2 +2 + =0

Since the second ellipse passes through the vertices of the rectangle, then we have the following
equations

9 + 12 + 4 + 6 + 4 + =0 (1)

9 12 + 4 + 6 4 + =0 (2)

9 12 + 4 6 + 4 + =0 (3)

9 + 12 + 4 6 4 + =0 (4)

Subtracting (2), (3), (4) from (1), we have

2 +8 =0

24 + 12 = 0

8 + 12 =0

From this, we can see that = = = 0. Hence, this justifies the second ellipse to be parallel to the
coordinate axes and satisfies the equation

+ =1

Since, the second ellipse passes through (0,4).

16
=1

= 16

Furthermore, it also passes through the vertices of the triangle.

9 4
+ =1

9 4
+ =1
16

= 12

Since the major axis for the second ellipse is along y-axis, then the equation for eccentricity can be
expressed as
= (1 )

1
=
4
1
=
2

Therefore, the eccentricity of the second ellipse is .